PENERAPAN FUZZY MULTIPLE CRITERIA DECISION MAKING (FMCDM) UNTUK MENGEVALUASI KUALITAS PELAYANAN - Mohammad Rizal Arief; Juli Sulaksono (Universitas Trunojoyo Madura, 2013)
The objective of this research is to measure quality level of service to customer of takwa-tofu (tahu takwa) industries in Kediri city. The theory employs in this research is Fuzzy Multi Criteria Decision Making (FMCDM) which is based on 6 service criterias stated by Gronross and the improvements (16 sub-criteria). Data use in this research is gathered by sampling technique with purposive sampling method which is done within one month against tofu consumers in Kediri city, especially related to service to consumers of takwatofu (tahu takwa) in Kediri. Multi criteria data is gathered from three takwa-tofu (tahu takwa) companies in Kediri city to measure the different service quality and bias. Analysis used is Fuzzy Multiple Criteria Decision Making (FMCDM) method. This research was success in measuring the level of service to customer based on the criteria above using FMCDM method and it is suggested that in term of service quality, LTH is in the highest position, however for the product quality, LTT is the best.